Safety Climate-A Study on Private Sector Chemical Companies in Kerala - Dhanisha, M; Johnson, B (International Journal of Psychosocial Rehabilitation, 2020)
The Indian chemical industry is a key contributor of national economy; it comprises small, medium and large scale units. It is the critical part of Indian economy has the huge potential for growth. A number of multinational and large Indian companies have invested in Indian Chemical sector and Government of India is rendering extensive support to give boost to this industry. Safety climate holds great potential in improving a company’s health and safety performance and reducing workplace injury rates. The present study aims to analyse the present safety climate in the private sector chemical companies in Kerala. The study also tries to analyse the effectiveness of present safety measures implemented by the companies. The result indicates that, almost all the safety measures are effective in the private sector chemical industry in Kerala. The article suggested some safety measures or guidelines those must be implemented by the chemical companies for ensuring the safety of their employees.